Isolated right atrium tuberculoma causing complete heart block - Ngow, Harris Abdullah; Wan Khairina, Wan Mohd Nowalid (BMJ Group, 2010)
Myocardial tuberculosis was rare even in the era before effective anti-tuberculous chemotherapy was available. It is becoming even rarer with improved anti-tuberculous treatment. It was usually an incidental finding during necropsy. In a case series reported by Custer and Charr, 1 they reviewed more than 14 000 deaths due to tuberculosis and found only 64 cases (0.5%) of tuberculosis involving the heart. In most cases the infection is either part of miliary tuberculosis or an extension of pericardial involvement. In the absence of these, it is presumed to be due to haematogenous or lymphatic dissemination.2 There is almost always a tuberculous focus elsewhere in the body; single isolated tuberculoma are very rare indeed. Complete heart block as a complication of myocardial tuberculosis has been described only rarely in medical literature. Thus far, only a limited number of cases have been reported, 3–7 and none of these was due to a tuberculoma in the right atrium.